Total Synthesis of (+)-Fusarisetin A: A Biomimetic Approach - Yin, Jun; Gao, Shuanhu (Synlett, 2014)
This article outlines our recent efforts to synthesize (+)-fusarisetin A, a naturally occurring 3-acyltetramic acid, by a route based on a hypothetical biosynthesis. Our research suggests that the biosynthesis of (+)-fusarisetin A might involve the aerobic oxidation of equisetin, possibly mediated by metal oxidants or by photochemically produced reactive oxygen species.
Keywords: radical reactions; total synthesis; biosynthesis; heterocycles; polycycles